International and comparative criminal justice and urban governance : convergence and divergence in global, national and local settings - Crawford, Thomas Adam Michael (Cambridge : Cambridge University Press, 2011)
'Criminal justice has traditionally been associated with the nation state, its legitimacy and its authority. The growing internationalisation of crime control raises crucial and complex questions about the future shape of justice and urban governance as these are experienced at local, national and international realms. The emergence of new international justice institutions such as the International Criminal Court, the greater movement of people and goods across national borders and the transfer of criminal justice policies between different jurisdictions all present novel challenges to criminal justice systems as well as our understandings of criminal justice. This volume of essays explores the implications and impact of criminal justice developments in an increasingly globalised world. It offers cutting-edge conceptual contributions from leading international commentators organised around the themes of international criminal justice institutions and practices; comparative penal policies; and international and comparative urban governance and crime control'--
Machine generated contents note: 1. International and comparative criminal justice and urban governance Adam Crawford; Part I. International Criminal Justice and Global Governance: 2. Unintended justice: the United Nations Security Council and international criminal governance James Cockayne; 3. The International Criminal Court and the state of the American exception Jason Ralph; 4. Universal crimes, universal justice?: The legitimacy of the international response to genocide, crimes against humanity and war crimes Chrisje Brants; 5. Locating victim communities within global justice and governance Mark Findlay; 6. Dealing with war crimes in Bosnia: retributive and restorative options through the eyes of the population Stephan Parmentier, Marta Valinas and Elmar Weitekamp; 7. Shaping penal policy from above? The role of the Grand Chamber of the European Court of Human Rights Dirk van Zyl Smit and Sonja Snacken; Part II. Comparative Penal Policies: 8. Penal comparisons: puzzling relations Michael Cavadino and James Dignan; 9. Why globalisation doesn't spell convergence: models of institutional variation and the comparative political economy of punishment Nicola Lacey; 10. Penal excess and penal exceptionalism: welfare and imprisonment in Anglophone and Scandinavian societies John Pratt; 11. The impact of multi-level governance on crime control and punishment Lesley McAra; 12. Explaining Canada's imprisonment rate: the inadequacy of simple explanations Cheryl Marie Webster and Anthony N. Doob; 13. US youth justice policy transfer in Canada: we'll take the symbols but not the substance Jane B. Sprott; 14. Liberty, equality and justice: democratic culture and punishment Susanne Karstedt; Part III. Comparative Crime Control and Urban Governance: 15. Victimhood of the national?: Denationalizing sovereignty in crime control Katja Franko Aas; 16. Cosmopolitan liberty in the age of terrorism Clive Walker; 17. Restorative justice and states' uneasy relationship with their publics Joanna Shapland; 18. Governing nodal governance: the'anchoring' of local security networks Hans Boutellier and Ronald van Steden; 19. From the shopping mall to the street corner: dynamics of exclusion in the governance of public space Adam Crawford; 20. Gating as governance: the boundaries spectrum in social and situational crime prevention Sarah Blandy; 21. French perspectives on threats to peace and local social order Sophie Body-Gendrot; 22. The question of scale in urban criminology Mariana Valverdec.
Includes bibliographical references and index.
Keywords: Criminal law -- Congresses; International crimes -- Congresses